Manajemen Perpustakaan Madrasah Ibtidaiyah Negeri 1 Rejang Lebong - Murniyanto, Murniyanto (Sekolah Tinggi Agama Islam Negeri (STAIN) Curup, 2017)
The library of Ibtidaiyah school Negeri 1 Rejang Lebong at this time still in developing thats why as an education component that support teaching learning process, every education united in the school that doing by the government and society should prepare a learning source, thats why the education it cant be run well if the teachers and the students are not supported by the learning source that needed for achieving teaching learning process. In the learning activities need to use a library as a way to make the students become smart, so the library functions to motivate the students, support learning activities, and help the students in achiving the goals of education in the school. The libarray for the students can add the knowledge if they can read therefernces and understand a management.